2012
DOI: 10.1158/1078-0432.ccr-12-0397
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Immunofluorescence Reveals the Signature of Active B-cell Receptor Signaling in Diffuse Large B-cell Lymphoma

Abstract: Purpose B cell receptor (BCR) mediated signaling is important in the pathogenesis of a subset of diffuse large B cell lymphomas (DLBCL) and the BCR-associated kinases SYK and BTK have recently emerged as potential therapeutic targets. We sought to identify a signature of activated BCR signaling in DLBCL to aid the identification of tumors that may be most likely to respond to BCR-pathway inhibition. Experimental Design We applied quantitative immunofluorescence (qIF) using antibodies to phosphorylated forms … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 54 publications
1
39
0
Order By: Relevance
“…28 Some sIg-negative DLBCL cell lines have been identified as oxidative phosphorylation tumors 28 and have been shown to be insensitive to BCR inhibition and stimulation in vitro. 30 Our study, taken together with previous investigations, [7][8][9]30 suggests that FIGURE 5. Immunoblotting showed that the levels of pSYK and pAKT in DLBCL, BCR + cell lines (OCI-LY1 and SU-DHL-4) were increased upon BCR cross-linking with 10 mg/mL rabbit anti-human IgM or goat anti-human IgG for 10 minutes.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…28 Some sIg-negative DLBCL cell lines have been identified as oxidative phosphorylation tumors 28 and have been shown to be insensitive to BCR inhibition and stimulation in vitro. 30 Our study, taken together with previous investigations, [7][8][9]30 suggests that FIGURE 5. Immunoblotting showed that the levels of pSYK and pAKT in DLBCL, BCR + cell lines (OCI-LY1 and SU-DHL-4) were increased upon BCR cross-linking with 10 mg/mL rabbit anti-human IgM or goat anti-human IgG for 10 minutes.…”
Section: Discussionsupporting
confidence: 71%
“…5 The phosphatidylinositol-3-kinase/ AKT (PI3K/AKT) pathway is one of the key pathways downstream of BCR engagement and is necessary to maintain the viability of DLBCL cells. 8,9 Preclinical studies have demonstrated that blocking BCR signaling may contribute to the silencing of the PI3K/AKT pathway and disrupt the growth of DLBCL cells in vitro. 8 Several ongoing clinical trials to assess the efficacy of BCR/PI3K/ AKT signaling inhibitors in treating B-cell malignancies, including DLBCL, have shown promising results.…”
mentioning
confidence: 99%
“…6 Btk is highly expressed in multiple myeloma, 7 acute myeloid leukemia (AML), 8 chronic lymphocytic leukemia (CLL), 9 and non-Hodgkin’s lymphoma (NHL). 10, 11 Given its importance, Btk has emerged as a molecular target for treatment of B-lineage leukemias and lymphomas. In addition, Btk plays a key role in macrophage polarization through signaling downstream of TLR4.…”
Section: Introductionmentioning
confidence: 99%
“…We first made several modifications to the model to accommodate the differences between normal BCR signaling and aberrant BCR signaling in ABC DLBCL. Instead of applying a temporal upstream stimulus, we assumed constitutive LYN and SYK phosphorylation as observed both in ABC DLBCL cell lines and in primary DLBCL patient samples (2,42) (see Materials and Methods). Additionally, we accounted for genetic alterations in members of the BCR signaling network in TMD8 compared to normal B cells.…”
Section: Resultsmentioning
confidence: 99%